2010
DOI: 10.1097/med.0b013e32833919cf
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone and type 2 diabetes

Abstract: Low testosterone levels are very commonly found in men with T2D and are associated with aging and obesity. Whether testosterone treatment in men with T2D decreases insulin resistance above that attributable to its fat-reducing effect is currently unknown. Future studies should compare testosterone treatment with lifestyle changes (exercise and weight loss measures), and other insulin-sensitizing agents. Until further evidence is available, testosterone therapy outside clinical trials should be reserved for dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(76 citation statements)
references
References 71 publications
1
71
0
4
Order By: Relevance
“…For example, in a recent prospective cohort study of men presenting for liver transplantation, low testosterone predicted mortality independently of the model of end-stage liver disease score, the standard score used to prioritise the allocation of liver transplants . It is evident from multiple studies that low testosterone identifies men with an adverse metabolic phenotype (Grossmann et al 2010). Diabetic men with low testosterone are significantly more likely to be obese or insulin resistant.…”
Section: End Organ Deficits Of Androgen Deficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in a recent prospective cohort study of men presenting for liver transplantation, low testosterone predicted mortality independently of the model of end-stage liver disease score, the standard score used to prioritise the allocation of liver transplants . It is evident from multiple studies that low testosterone identifies men with an adverse metabolic phenotype (Grossmann et al 2010). Diabetic men with low testosterone are significantly more likely to be obese or insulin resistant.…”
Section: End Organ Deficits Of Androgen Deficiencymentioning
confidence: 99%
“…In prospective studies, reviewed in detail elsewhere (Grossmann et al 2010) the inverse association of low testosterone with metabolic syndrome or diabetes is less consistent for free testosterone compared with total testosterone. This is because of the confounding effects of SHBG, itself being a strong associate of insulin resistance (Wallace et al 2013).…”
Section: End Organ Deficits Of Androgen Deficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…In women, it is well known that hyperandrogenism is often associated with increased intra-abdominal fat accumulation and the metabolic syndrome (as for the case of polycystic ovary syndrome; Gambineri et al 2009), and the decline of estrogen after menopause is known to determine an increase in intraabdominal fat mass (Lobo 2008). In men, testosterone deficiency in hypogonadic individuals is associated with a significant change in body composition (especially featured by an increase in fat mass) and with the frequent presence of dysmetabolisms (Barrett-Connor 1992, Barud et al 2002, Grossmann et al 2010, Traish et al 2011. Testosterone replacement therapy in patients with reduced testosterone levels has been shown to produce a significant metabolic amelioration, not only related to body weight but also related to the glucose and lipid profile (Traish et al 2011).…”
Section: Brown Adipose Tissue and Obesitymentioning
confidence: 99%
“…Accordingly, an increase in muscle mass and a reciprocal decrease in fat mass have been reported in randomized, placebo-controlled trials of testosterone therapy in elderly nondiabetic men (1, 2, 3, 4). However, the changes in body composition are modest, and this may explain why only a few, but not all, of these studies have found a positive effect on the measures of insulin sensitivity (1, 4,5). A better understanding of the mechanisms involved in androgen action is needed to establish to what extent testosterone deficiency causally contributes to insulin resistance and type 2 diabetes in elderly men, and to clarify potential beneficial effects of testosterone replacement therapy on insulin sensitivity.…”
Section: Introductionmentioning
confidence: 99%